Pengaruh Akuntansi Keprilakuan terhadap Kinerja Karyawan di KSP Kopdit Pintu Air Rotat - Maria Silviani Barek Atakiwang; Siktania Maria Dilliana; Paulus Libu Lamawitak (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to find out whether behavioral accounting has an effect on employee performance at KSP Kopdit Pintu Air Rotat. The data used in this research uses primary data where primary data collection is carried out by distributing questionnaires to employees of KSP Kopdit Pintu Air Rotat. The sampling technique used in this research is probability sampling using the Simple Random Sampling Technique method, namely sampling is carried out randomly without paying attention to strata in the population so that the number of samples obtained in this research is 43 employees of the Main Branch of KSP Kopdit Pintu Air Rotat. The data collection process was carried out by distributing questionnaires to respondents. Where the research instrument uses a Likert scale. The data analysis method uses simple linear regression analysis with the help of the SPSS program. The results of this research show that behavioral accounting variables have a significant effect on employee performance at KSP Kopdit Pintu Air Rotat. This can be seen from the results of the partial test (t test) with a significant value of 0.001 ≤ 0.005. The results of this research are also supported by the results of descriptive analysis of variables, the average score of the behavioral accounting variable is 83.13%, while the average score of the employee performance variable is 79.41%.